Copper-Catalyzed Synthesis of Coumarins. A Mini-Review - Renato Dalpozzo (MDPI AG, 2021)
Coumarin (2H-chromen-2-one) derivatives have important uses in medicinal and synthetic chemistry, for example, as fluorescent probes. These properties have prompted chemists to develop efficient synthetic methods to synthesize the coumarin core and/or to functionalize it. In this context, many metal-catalyzed syntheses of coumarins have been introduced; among them, copper-catalyzed reactions appear to be very promising owing to the non-toxicity and cheapness of copper complexes. In this mini-review, the results in this field are summarized. We hope to stimulate other applications of these complexes in the preparation of coumarin derivatives.